TRANSPORT SUPPORT FOR HOTEL AND RESTAURANT SERVICES IN THE CURRENT CONDITIONS OF TERRITORIAL COMMUNITIES DEVELOPMENT - STEHNEI, Marianna; NOD, Orshoia; BERGHAUER , Sándor; PROKOPETS, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article investigates the role of transport support in shaping the quality of hotel and restaurant services in the context of the development of territorial communities. It is noted that the development of the hotel and restaurant business within territorial communities is an important attribute of the area's image, attracting investments, generating tax revenues, and creating jobs within the community. Well-organized transport services for citizens and guests, as well as the presence of developed transport systems in territorial communities, are crucial for economic and social development. It has been proven that high-quality transport support is an important condition for the competitiveness of a region's (community's) tourism product, which is why representatives of the tourism and hotel-restaurant business are interested in its optimization, development, and diversification.The state of transport support for community development has been analyzed, highlighting the main trends, including the growing role and predominance of automobile and railway transport, the deterioration of transport service quality, the aging of public transport fleets, the weak alignment of routes with the needs of citizens and businesses, and the declining economic accessibility of transport for low-income citizens. These problems are exacerbated by the full-scale war in Ukraine.To optimize transport support for hotel and restaurant services in territorial communities, a model is proposed that aims to improve the accessibility of tourist sites through the cooperation of local communities and enterprises, infrastructure development, and the use of modern technologies. At the local level, the implementation of the model for optimizing transport support for hotel and restaurant services can be carried out using several tools, including the development and improvement of local transport routes to enhance the accessibility of key tourist sites; investment in transport infrastructure, such as improving road surfaces, creating convenient public transport stops, and parking zones; cooperation between local authorities and tourism enterprises in creating joint information centers and organizing promotional campaigns; and public-private partnerships.
Keywords: hotel and restaurant services; transport system; transport support; territorial communities; model for optimizing transport support for hotel and restaurant services